Memorizing lyrics and performing from memory : a study of professional singers’ approaches to foreign language repertoire - Rinta, Laura Maria (Taideyliopiston Sibelius-Akatemia, 2023)
The overarching aim of my research is to investigate the approaches professional singers use to memorize lyrics and remember the lyrics during a performance. I focus especially on the challenge of singing and performing in a language other than one’s mother tongue since it is quite common among singers. The research questions that will address this overarching aim are: • What different strategies do singers use to memorize lyrics? • What kind of strategies do singers use to remember song lyrics while performing on stage and what coping mechanisms do they use if they forget the lyrics? • How does the language of the song influence the memorization of lyrics and remembering them during performance? Based on my research results, using various strategies based on different memory systems is the most effective way to memorize lyrics. It is recommended to memorize the song by deliberate memorization training instead of relying only on motor memory. By memorizing lyrics in deliberate ways, for example by using structural memory or emotional memory, when performing, a singer can rely on different memory systems and be able to cope in a situation where the motor and auditory based association chains fail. Strategies to memorize the lyrics include for example studying the meaning of the text, translating it into one’s mother tongue if necessary, memorizing the lyrics phonetically, writing the lyrics on paper by hand, listening to a recording of the song and singing along with the recording, as well as attaching emotions and an interpretation to the lyrics, and making a storyline to structure the song. When forgetting the lyrics on stage common coping mechanisms include singing the lyrics of the previous verse or singing the same lyrics twice, singing without words for example scatting, humming, or singing with relevant syllables as well as taking a break and indicating to the band to play a solo or to continue longer in the part they are already playing.
Keywords: sanoitukset; laulajat; laulaminen; laulut; musiikki; muisti (kognitio); muusikot; esittävät taiteet; Glomas